PENGARUH PEMAHAMAN KODE ETIK PROFESI AKUNTAN TERHADAP PERILAKU ETIS PADA MAHASISWA STIE NASIONAL BANJARMASIN - Soedjatmiko -; Hilmi Abdullah; Nor Asiah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,The purpose of this study is to provide empirical evidence of the influence of understanding the ethical code of the accountant profession against ethical behavior in accounting students STIENAS Banjarmasin.Population and sample in this study are students majoring in accounting given some questions about understanding the ethical code of accountant profession and ethical behavior. The method used in this research is quantitative descriptive to describe the understanding of ethics code of accountant profession to the ethical behavior of STIE students of Banjarmasin.The results of this study indicate that understanding the ethical code of the accountant profession affect the ethical behavior of the students of National STIE Banjarmasin.